Empirical study on the relationship between exchange rate and stock investment in Asia. - Chiam, Thor Eng (2014)
Previous studies conducted have displayed a strong relationship between interest rates and investments, as well as between interest rates and exchange rates. However, any direct relationship between investments and exchange rates has yet to be established. Following the article ''Most Regional Exchanges Decline As US Dollar Nosedives", which was published on 4 July 1994 in the Bangkok Post, we have decided to carry out an investigation into the relationship between exchange rates and stock investments in various Asian countries. These countries include Hong Kong, Japan, Malaysia and Singapore.